EFFECT OF BREASTFEEDING DURING PREGNANCY ON THE OCCURRENCE OF MISCARRIAGE AND PRETERM LABOUR (Iraqi Journal of Medical Sciences, 2016)
Background:Many mothers breastfeed their babies while they are pregnant. Objective:To explore whether breastfeeding during pregnancy increases the risk of miscarriage and preterm births.Methods: A case-control study conducted in Al-Mawany General Hospital through a period extended from first of September 2011 till the first of September 2012. Two hundred fifteen pregnant women who breastfed during pregnancy and two hundred eighty pregnant who weren't breastfeeding during pregnancy were studied. Demographic data, frequency of miscarriage and preterm deliveries and neonatal birth weight were compared between the two groups. Chi-Square and student t-test were used to compare the result. Significant difference was considered when P value < 0.05.Result:The frequency of miscarriage among those who breastfed their babies during pregnancy were significantly lower than among those who didn’t breastfed during pregnancy, this was unaffected by exclusiveness of breastfeeding, however, there was statistically insignificant difference in the frequency of preterm deliveries and in the birth weight between the two groups.Conclusions:Breastfeeding doesn't increase the risk of miscarriage or preterm births neither does it affect neonatal birth weight. Keywords:Miscarriage, breastfeeding, preterm labour, exclusive breastfeeding, non exclusive breastfeeding
Keywords: Miscarriage; breastfeeding; preterm labour; exclusive breastfeeding; non exclusive breastfeeding